2018
DOI: 10.14419/ijet.v7i3.24.17301
|View full text |Cite
|
Sign up to set email alerts
|

Safety Advice and Safety Participation in OSHMS among OHSAS 18001 certified Malaysian Manufacturing Companies

Abstract: Lack of safety participation in Occupational Safety, Health and Environment Management System (OSHMS) has exposed employees to high risk of work hazards resulting in high occupational accidents. This does not only affect employee’s morale towards work, but employer also needs to bear the cost of recovery and its effect to its reputation. This study was carried out to determine the relationship of safety capital (management safety commitment, safety training, extrinsic reward, intrinsic reward, employee involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, a firm can promote itself as the safest place to work in the relative industry by showing statistical facts regarding the number of injuries in the past years. Another critical dimension is provided by Kheng-Khor and Surienty [10], explaining the relationship between a safer workplace and employee involvement.…”
Section: Benefits Incurred From Oshad-sf Implementation: a Business P...mentioning
confidence: 99%
“…For example, a firm can promote itself as the safest place to work in the relative industry by showing statistical facts regarding the number of injuries in the past years. Another critical dimension is provided by Kheng-Khor and Surienty [10], explaining the relationship between a safer workplace and employee involvement.…”
Section: Benefits Incurred From Oshad-sf Implementation: a Business P...mentioning
confidence: 99%
“…6 Another aim of safety communication is making sure that everyone comprehends their roles and responsibilities concerning OSH, regardless of the safety managers play significant roles in ensuring all stakeholders are fully informed about OSH policies, practices, concerns, and other information. 4,7 It is revealed that OSH communication mediates the association between safety culture and safety performance partially. 8 However, as mentioned earlier, accidents still happened due to the ineffectiveness of OSH communication.…”
Section: Introductionmentioning
confidence: 99%